IDENTIFIKASI DEFISIENSI NUTRISI DI PERKEBUNAN KELAPA SAWIT PT. SMART Tbk., MENGGUNAKAN PENGINDERAAN JAUH - Wijaya, Nurriyadin Akbar; Wardati, Wardati; Silalahi, Divo D. (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
1. Mahasiswa Fakultas Pertanian Universitas Riau2. Dosen Fakultas Pertanian Universitas Riau The purpose of this research is to identify nutrient deficiency by using remote sensing in palm oil plantation. The research was conducted in palm oil plantation, PT. SMART Tbk (Sinarmas Agro Resources and Technology Tbk), Kandista Garden, Kandis, Siak Regency, Riau. This research had been conducted for six months in March to August 2017. The total area used in this research was 1628,59 ha. This research used survey method consisting of several stages viz. 1) Establish sample location by looking at several aspects in the determination of land availability, soil fertility, and land characteristics. 2) Determinate point sample done homogeneously by looking at the health and normal condition of palm oilthat will affect the plot location. 3) Leaf analysis, soil analysis and remotesensing used image processing. The data obtained were analyzed using regression analysis, to determine the correlation of satellite color and actual data in the field. Parameters used were the analysis of nutritioncontent, analysis of nutritioncontent with remote sensing. The resultsshowed that nutrient content of N, P and K of palm oil leaves contain no nutrient deficiency. Nutrient N and P content in leaves have a better accuracy than model prediction results compared with K content. Based on the analysis, composite bands: red, green, bluewere unstable and unconsistent in representing plant nutrient content, this may be influenced by imaging resolution obtained. Keywords: Elaeis guineensis Jacq., Pupuk NPK, Citra Sentinel-2